The rapidly changing Arctic and its societal implications. (7th September 2021) - Ford, James D.; Pearce, Tristan; Canosa, Ivan Villaverde; Harper, Sherilee
Abstract: The Arctic is undergoing rapid climate change and is projected to experience the most warming this century of any world region. We review the societal aspects of these current and projected changes. Indigenous knowledge and local knowledge holders living in communities across the Arctic have detected unprecedented increases in temperature, altered precipitation regimes, and changing weather patterns, documenting impacts on terrestrial and marine environments. These local observations situate climate change as one of multiple interacting stressors. Arctic societies have exhibited resilience to climate change, but vulnerabilities are emerging at the nexus of changing environmental conditions and socioeconomic pressures. Infrastructure is highly susceptible to permafrost thaw, coastal erosion, and sea level rise, compounded by the age of infrastructure, maintenance challenges, and cost of adapting. Livelihoods and cultural activities linked to subsistence harvesting have been affected by changes to wildlife, with coping mechanisms undermined by long‐term processes of land dispossession and landscape fragmentation. Reduced sea ice coverage and changing ice dynamics are creating opportunities for enhanced shipping, oil and gas production, and deep‐water fisheries. Legal, infrastructural, economic, and climatic challenges are expected to constrain such developments, with concerns over the distribution of potential benefits. Adaptation is already taking place in some sectors and regions, with efforts directly targeting climate impacts and also addressing underlying determinants of vulnerability. Barriers and limits to adapting are evident. Research that develops projections of future climate impacts is advancing, but studies examining the implications of such changes for communities or economies remain in their infancy. This article is categorized under: Trans‐Disciplinary Perspectives > Regional Reviews Abstract : The societal impacts of climate change in the Arctic will be shaped by the unique livelihoods, cultures, and worldviews of those living in the region (photo: Graham McDowell).